Co-infection of Candidatus Piscichlamydia Trichopodus (Order Chlamydiales) and Henneguya sp. (Myxosporea, Myxobolidae) in Snakeskin Gourami Trichopodus pectoralis (Regan 1910) - Dinh-Hung, Nguyen; Dong, Ha Thanh; Soontara, Chayanit; Rodkhum, Channarong; Nimitkul, Sukkrit; Srisapoome, Prapansak; Kayansamruaj, Pattanapon; Chatchaiphan, Satid (Frontiers in Veterinary Science, 2022)
The present study describes a simultaneous infection of a novel Chlamydia-like organism (CLO) with a Myxozoa parasite, Henneguya sp. in snakeskin gourami Trichopodus pectoralis in Thailand. A new CLO is proposed “Candidatus Piscichlamydia trichopodus” (CPT) based on 16S rRNA phylogenetic analysis. Systemic intracellular CPT infection was confirmed by histological examination, in situ hybridization, PCR assay, and sequencing of 16S rRNA. This novel pathogen belongs to the order Chlamydiales but differs in certain aspects from other species. The histopathological changes associated with CPT infection were different from the typical pathological lesions of epitheliocystis caused by previously known CLO. Unlike other CLO, CPT localized in the connective tissue rather than in the epithelial cells and formed smaller clumps of intracellular bacteria that stained dark blue with hematoxylin. On the other hand, typical myxospores of the genus Henneguya with tails were observed in the gill sections. Infection with Henneguya sp. resulted in extensive destruction of the gill filaments, most likely leading to respiratory distress. Due to the frequency of co-infections and the unavailability of culture methods for CLO and Henneguya sp., it was difficult to determine which pathogens were directly responsible for the associated mortality. However, co-infections may increase the negative impact on the host and the severity of the disease. Given the commercial importance of the snakeskin gourami and its significant aquaculture potential, the findings of this study are important for further studies on disease prevention.